1.5(9b-27)=36

Simple and best practice solution for 1.5(9b-27)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.5(9b-27)=36 equation:


Simplifying
1.5(9b + -27) = 36

Reorder the terms:
1.5(-27 + 9b) = 36
(-27 * 1.5 + 9b * 1.5) = 36
(-40.5 + 13.5b) = 36

Solving
-40.5 + 13.5b = 36

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '40.5' to each side of the equation.
-40.5 + 40.5 + 13.5b = 36 + 40.5

Combine like terms: -40.5 + 40.5 = 0.0
0.0 + 13.5b = 36 + 40.5
13.5b = 36 + 40.5

Combine like terms: 36 + 40.5 = 76.5
13.5b = 76.5

Divide each side by '13.5'.
b = 5.666666667

Simplifying
b = 5.666666667

See similar equations:

| 1=y(4x+1) | | 0.20+0.35(50)=31.5 | | 2x+1=13-x | | -4(2t+7)=-44 | | 2x-7y=11fory | | 4x+7=-4x+20 | | -12x+12x+8=16 | | T-15=76 | | 6y+-15=9 | | 7=-7-(p-8) | | 8x+0.5=7x+2 | | 2m+13=25 | | 19m+9n=16 | | 2x+4=4x+16 | | 5x+12=-42-4x | | 9=q-4 | | 5(f-9)=-45 | | n/3-6=10 | | 4x+5=-2+2 | | 9=a-4 | | 8(s-6)=-100 | | y/-23 | | 2(x^2+4)=0 | | 2P(A)=P(B)=5/13 | | 64p=16 | | A=3(a*a)*5a+7(a*a)*2a+7 | | 2P(A)=5/13 | | -10-3x-5x=-42 | | 70=5(4i+2) | | T+32=420 | | 2*n-(n-7)=12 | | 3(t+2)=-9 |

Equations solver categories